Mixed convection boundary layer flow on a horizontal circular cylinder in a nanofluid with viscous dissipation effect - Muhammad Khairul Anuar, Mohamed; Norhafizah, Md Sarif; Nor Aida Zuraimi, Md Noar; Mohd Zuki, Salleh; Anuar, Mohd Ishak (UTM Press, 2018)
In this study, the mathematical modeling for the mixed convection boundary layer flow past a horizontal circular cylinder in a nanofluid with the presence of viscous dissipation effect is considered. The system of governing non-linear partial differential equations are first transformed to a more convenient form before being solved numerically using the Keller-box method. Numerical solutions are obtained for the reduced Nusselt number, Sherwood number and skin friction coefficient as well as the concentration, the temperature and the velocity profiles. The features of the flow and heat transfer characteristics for various values of the Eckert number, Lewis number, Brownian motion parameter, thermophoresis parameter, mixed convection parameter, concentration mixed convection parameter and Prandtl number are analyzed and discussed. It is suggested that the presence of buoyancy forces in mixed convection delayed the separation in assisting flow. Further, the Nusselt number decreases while Sherwood number increases with the increase of Brownian parameter, thermophoresis parameter and the Lewis number. It is worth mentioning that the results in this paper is important especially in understanding the nanofluid parameters behaviour as cooling medium in such applications like transformer liquid submersion system, power supply unit in supercomputer and liquid cooling for electronic components like capacitor and transistor.